Cross-dynastic intergenerational altruism - Frikk Nesje (University of Heidelberg, Department of Economics, 2020)
Decisions with long-term consequences require comparing utility derived from present consumption to future welfare. But can we infer socially relevant intertemporal preferences from saving behavior? I allow for a decomposition of the present generation's preference for the next generation into its dynastic and crossdynastic counterparts, in the form of welfare weights on the next generation in the own dynasty and other dynasties. Welfare weights on other dynasties can be motivated by a concern for sustainability, or if descendants may move or marry outside the dynasty. With such cross-dynastic intergenerational altruism, savings for one's own descendants benefit present members of other dynasties, giving rise to preference externalities. I find that socially relevant intertemporal preferences may not be inferred from saving behavior if there is cross-dynastic intergenerational altruism. I also show that the external effect of present saving decreases over time. This means that intertemporal preferences inferred from saving behavior are time-inconsistent, unless cross-dynastic intergenerational altruism is accounted for.
urn:nbn:de:bsz:16-heidok-279779
Keywords: D64; D71; H43; Q01; Q54; 330; Intergenerational altruism; social discounting; time-inconsistency; declining discount rates; generalized consumption Euler equations; interdependent utility; isolation paradox